2007
DOI: 10.1111/j.1469-7580.2007.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of the triangular fibrocartilage complex of the wrist: regional variations in cartilage phenotype

Abstract: The triangular fibrocartilage complex (TFCC) transmits load from the wrist to the ulna and stabilizes the distal radioulnar joint. Damage to it is a major cause of wrist pain. Although its basic structure is well established, little is known of its molecular composition. We have analysed the immunohistochemical labelling pattern of the extracellular matrix of the articular disc and the meniscal homologue of the TFCC in nine elderly individuals (age range 69 -96 years), using a panel of monoclonal antibodies di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 32 publications
(16 reference statements)
0
14
0
Order By: Relevance
“…The ACAN gene encodes aggrecan, an important proteoglycan molecule within the extracellular matrix of ligaments and many other musculoskeletal tissues; most importantly, aggrecan is a major structural component of human cartilage and fibrocartilage [18][19][20][21] . Aggrecan is a large, aggregating proteoglycan that plays a critical role in mediating chondrocytechondrocyte and chondrocyte-matrix interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The ACAN gene encodes aggrecan, an important proteoglycan molecule within the extracellular matrix of ligaments and many other musculoskeletal tissues; most importantly, aggrecan is a major structural component of human cartilage and fibrocartilage [18][19][20][21] . Aggrecan is a large, aggregating proteoglycan that plays a critical role in mediating chondrocytechondrocyte and chondrocyte-matrix interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The changes comprise reduced cellularity, loss of elastic fibers, mucoid degeneration of the ground substance, exposure of collagen fibers, fibrillation, erosion, ulceration, abnormal thinning, and, ultimately, disc perforation. An immunohistochemical study of the TFCC [8] in nine elderly individuals demonstrated that the ulnocarpal disc is a fibrocartilaginous structure which labels for type II collagen and aggregan, a proteoglycan-typical marker of a cartilaginous phenotype, whereas the meniscal homologue of the TFCC is a more fibrous structure. …”
Section: Introductionmentioning
confidence: 98%
“…As a result, its insertion angle is not physically constrained and it experiences multiaxial loading during in vivo loading [15]. In particular, during wrist adduction, a joint motion partially controlled by the FCU muscle, the FCU tendon-pisiform enthesis is subject to high shear strains that have been linked to a fibrocartilage-like structure and composition in other tendons [16, 17]. Interestingly, the FCU insertion site is known to contain high levels of collagen II and aggrecan, a large proteoglycan typically associated with cartilaginous tissues that experience predominantly compression and shear [15].…”
Section: Introductionmentioning
confidence: 99%